Chromosome Errors in Human Eggs Shape Natural Fertility Over Reproductive Life Span. Issue 7 (July 2020) - Gruhn, Jennifer R.; Zielinska, Agata P.; Shukla, Vallari; Blanshard, Robert; Capalbo, Antonio; Cimadomo, Danilo; Nikiforov, Dmitry; Chan, Andrew Chi-Ho; Newnham, Louise J.; Vogel, Ivan; Scarica, Catello; Krapchev, Marta; et al.
Abstract : (Abstracted from Science 2019;365:1466–1469) While it is understood that young females (≥13 years to early 20s) and women of advancing maternal age (AMA, mid-30s or older) have reduced fertility rates, the exact mechanisms behind this feature of the fertility curve remain unclear. Because chromosomal errors and aneuploidy cause a significant amount of pregnancy loss and congenital disorders in women of advanced maternal age, meiotic error rates throughout the entire reproductive life span may shape natural fertility.